Hipnoterapi Untuk Menurunkan Nyeri Dismenore : Tinjauan Pustaka - Adzkia, Maratul; Kartika, Imelda Rahmayunia (Universitas Fort De Kock Bukittinggi, 2020)
This literature review was made aiming to increase knowledge and enrich our Evidence Based health workers about Hypnoteraphy Treatment for menstrual pain. By doing a number of stages in the making, namely looking for his journal on Google (Proques, Google Education, Pubmed) with the keywords